Republic of Croatia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Croatia. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that the economic expansion continues, driven primarily by private consumption and exports of goods and services. Discussions primarily focused on increasing the economy's flexibility and resilience. Fiscal performance has been strong, however, the materialization of contingent liabilities from government guarantees is likely to reduce the overall surplus. Low public and private investment, and continued emigration appear to weigh on medium-term growth prospects. Downside risks in the near-term stem could be due to possible changes in regional or global economic and financial conditions, and the further realization of contingent liabilities. The IMF staff advocated for a moderately faster fiscal adjustment. The report recommends accelerating the pace of debt reduction that would build fiscal space and help reduce downside risks. The Central Bank may need to address potentially tighter external conditions while continuing with strong bank supervision and macroprudential policies. Additional measures to prevent excessive household borrowing could be considered if needed.